2014
DOI: 10.1063/1.4898616
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interaction in oxygenated alpha Fe-phthalocyanines

Abstract: Abstract. Alpha iron phthalocyanines ( -FePc) oxygenated at low temperatures were investigated with the help of 57 Fe Mössbauer spectroscopy, magnetization measurements (SQUID) and X-ray diffractometry (XRD). Mössbauer spectroscopy revealed that upon oxygenation of -FePc, new species were formed which could be associated with Fe III Pc oxygen adducts. Unexpectedly, magnetically split spectrum of oxygenated -FePc was observed below 20 K. In-field Mössbauer spectra in a 5 T external magnetic field at 5K and magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…An analysis of spectra showed that the magnitude of the internal magnetic field remained unchanged when an external magnetic field was applied. This confirms the presence of an antiferromagnetic interaction in the studied system [ 43 ]. The antiferromagnetism of this sample was also verified by measurements of its magnetic susceptibility [ 43 ].…”
Section: Temperature-dependent Spin Transitions and Antiferromagnesupporting
confidence: 84%
See 4 more Smart Citations
“…An analysis of spectra showed that the magnitude of the internal magnetic field remained unchanged when an external magnetic field was applied. This confirms the presence of an antiferromagnetic interaction in the studied system [ 43 ]. The antiferromagnetism of this sample was also verified by measurements of its magnetic susceptibility [ 43 ].…”
Section: Temperature-dependent Spin Transitions and Antiferromagnesupporting
confidence: 84%
“…This confirms the presence of an antiferromagnetic interaction in the studied system [ 43 ]. The antiferromagnetism of this sample was also verified by measurements of its magnetic susceptibility [ 43 ].…”
Section: Temperature-dependent Spin Transitions and Antiferromagnesupporting
confidence: 84%
See 3 more Smart Citations